Obesity and lung function among healthy employees of a regional urban medical college in odisha, India - PRANATI NANDA,; NIBEDITA PRIYADARSINI,; AMRITA SATPATHY,; JOY P. NANDA, (International Journal of Pharma and Bio Sciences, 2017)
Obesity associated restrictive lung capacity is poorly understood, notably in an otherwise healthy population. To evaluate this relationship, we recruited non-smokers without any pulmonary disorders & examined their body mass index (BMI) and standard pulmonary tests. Following consent and eligibility determination, 81 healthy non-smokers from 354 employees at a regional medical college were considered. Overall, BMI was inversely correlated with MVV15 (r=-0.24, p=0.03). Analysis of mean Maximum Voluntary Ventilation (MVV15) stratified by BMI categories showed an inverse gradient MVV15 by ascending obesity categories (normal-overweight-obesity). In one multiple regression analyses, after adjusting for age, gender, FEV1/FVC ratio, overall BMI contributed to a quarter of a point lowering of MVV15 (beta=-0.248, t=2.36, p=0.02), with the model explaining 26% of variance (R2=25.5). In a separate equation with same covariates, obese participants (BMI>=30) contributed almost a 4-point reduction in MVV15 (beta=3.91, t=2.73, p=0.007) with the latter model explaining 28% of variance (R2=27.6%) in MVV15. Obesity in healthy individuals may produce restrictive pulmonary function due to differential distribution of adipose tissue in the chest and abdomen, which needs further investigation.